Allergen-specific CD8(+) T cells and atopic disease. - Seneviratne, S; Jones, L; King, A; Black, A; Powell, S; McMichael, A; Ogg, G (2002)
Considerable evidence suggests that IL-10 may have a role in the manifestation of atopic disease. We sought to test the hypothesis that at the single cell level, allergen-specific T cells have diminished IL-10 production capacity in severely affected atopics compared with asymptomatic atopics. We defined three A*0201-restricted Der p 1 CD8(+) T cell epitopes. Using human leukocyte antigen-A*0201-peptide (HLA-A*0201-peptide) tetrameric complexes and enzyme-linked immunospot assays to analyze peripheral blood mononuclear cells from A*0201-positive severely symptomatic atopics, asymptomatic atopics, and nonatopic controls, we observed a significant association between the frequency of the Der p 1-specific CD8(+) T cells and disease activity. The specific T cells expressed an antigen-experienced cell surface phenotype, and 45.7% were positive for cutaneous lymphocyte-associated antigen. The specific T cells were able to produce IFN-gamma efficiently, but their IL-10 production was significantly reduced in severely affected atopics. In contrast, viral-specific CD8(+) T cells were able to produce equivalent amounts of IL-10 in the severely affected atopics compared with asymptomatic atopics and nonatopics. Through defining the first human atopic allergen HLA class I epitopes, we have provided a possible cellular mechanism to link the previous association of low IL-10 levels and severe atopic disease. These data are consistent with a role for CD8(+) T cells in atopic disease pathogenesis and may provide a basis for future T cell immunotherapy strategies.